2019
DOI: 10.3390/polym11111813
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Cellulose Nanofibers via Eco-friendly Supercritical Carbon Dioxide Treatment Followed by Mild Acid Hydrolysis and the Fabrication of Cellulose Nanopapers

Abstract: The conventional isolation of cellulose nanofibers (CNFs) process involves high energy input which leads to compromising the pulp fiber’s physical and chemical properties, in addition to the issue of elemental chlorine-based bleaching, which is associated with serious environmental issues. This study investigates the characteristic functional properties of CNFs extracted via total chlorine-free (TCF) bleached kenaf fiber followed by an eco-friendly supercritical carbon dioxide (SC-CO2) treatment process. The F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 44 publications
6
24
0
Order By: Relevance
“…These results are consistent with the ones presented in this study. This is consistent with the report of Atiqah et al [44] that amorphous portions like hemicellulose and lignin were removed after applying alkali and bleaching treatment on raw kenaf fibre. Figure 3 shows the native and micro cellulose fibre spectra obtained by chemical treatment.…”
Section: Structural Characterizationsupporting
confidence: 93%
“…These results are consistent with the ones presented in this study. This is consistent with the report of Atiqah et al [44] that amorphous portions like hemicellulose and lignin were removed after applying alkali and bleaching treatment on raw kenaf fibre. Figure 3 shows the native and micro cellulose fibre spectra obtained by chemical treatment.…”
Section: Structural Characterizationsupporting
confidence: 93%
“…These functional group bonds represent cellulose nanofibre, as reported in previous studies [ 28 , 34 ]. The functional group analysis confirmed the successful isolation of CNF using combined supercritical carbon dioxide and high-pressure homogenisation [ 33 ].…”
Section: Resultsmentioning
confidence: 91%
“…These confirmed that the CNF isolated could not be reversed back to its raw material or change its properties. Even at high voltage [ 33 ]. This means that the isolation process produced a stable cellulose nanofibre.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the modified biofilms in Figure 2g-f exhibited dense structure with tightly packed stratified cross-sections as the fibre loading increased compared with unmodified biofilms. As the percent loading increased, the biofilm's porosity decreased, suggesting the significance of homogenous and well dispersed CNFs in the macroalgae matrix, which was fused due to the interaction and intermolecular hydrogen bonding [27]. The reduction of the biopolymer film's porous surface could be attributed to the increase in CNFs in the macroalgae matrix, indicating an increase in mechanical strength.…”
Section: Morphology Of the Unmodified And Modified Macroalgae/cnf Biomentioning
confidence: 99%